Chlorophyll content and degrees day accumulation in passion fruit species in the Southwest of Goias, Brazil - Dias do Valle, Karminne; Souza Chaves, Vanessa Brenda; Pereira, Laísse Danielle; Fialho dos Reis, Edésio; Hurtado Salazar, Alejandro; Pereira da Silva, Danielle Fabíola (Comunicata Scientiae, 2018)
Brazil is considered the world’s largest passion fruit producer, which benefits the entire crop chain of production and generates demand for production. The aim of this study was to evaluate the growth, thermal requirements and leaf morphological aspects of passion fruit species. The experiment was conducted at the Federal University of Goias (UFG)- Jataí, evaluating the following characteristics: leaf area, chlorophyll content (TCC) and thermal accumulation, being expressed in days after planting. To determine the total chlorophyll content, assessments were made in the middle third of the leaf blade, evaluating the accumulation of thermal units until flowering, from the average temperatures of the region. The daily temperature data were obtained from the meteorological station of the UFG - Jataí (17º53’08” S and 51º40’12” O). The cultivar FB 200 and Maracujazeiro-azedo presented higher leaf area, having the last one higher chlorophyll content in leaves and FB 200 presented lower demand in thermal units accumulation, proving its precocity.